HPV typing of high-grade dysplasia (CIN III) in cone biopsies of 38 HPV-vaccinated women - Ondič, Ondrej; Kašpírková, Jana; Májek, Ondřej; Kinkorová, Iva (Virchows Archiv, 2014)
HPV-vaccinated women develop CIN III very rarely. We have identified a study group of 38 such patients and showed that a specific HPV genotype prevalence in those cases equals the prevalence of HPV genotypes in CIN III present in the general Czech population. In all cases, CIN III was diagnosed within 3 years after having completed the HPV vaccination. We conclude that dysplasia was present before the vaccination in those women. A history of abnormal pre-vaccination PAP smear result (present in 78 % of women in the study group) and age of over 17 by the time of vaccination completion (97 % of women in the study group) are identified as probable factors increasing the risk of CIN III development after HPV vaccination.
Keywords: Biopsy; vakcíny proti papilomavirům; vakcinace; Humans; Vaccination; Female; dospělí; nádory děložního čípku; Genotype; lidé; biopsie; Papillomaviridae; Adult; ženské pohlaví; dysplazie děložního hrdla; Adolescent; Uterine Cervical Neoplasms; genotyp; Uterine Cervical Dysplasia; Papillomavirus Vaccines; mladiství